Estado, ideologia e educação no jornal "Tribuna dos Municípios" de Irati-PR (1954-1959) - Zanlorenzi, Claudia Maria Petchak (2006)
The present study refers to the research conducted in the Post-graduation course at UEPG with the theme State, Ideology and Education in the "Tribuna dos Municípios" from Irati (1954-1959). This study it had as a general objective: to analyze the relation between the State and the Education through the articles published in the periodical Tribuna dos Municipios from Irati - PR, within the period from 1954 to 1959. In the course of the inquiry it is investigated how the periodical expresses on the education and it is also analyzed the interests of the social groups on the education, as well as the ideological links present in the topics on the education propagated by the periodical. To do so, the analysis of the present study had as approach the historical materialism, because it provides a vision of totality, interconnection of facts and contextualization, as also allows emphasizing the historical dimension of the social processes.The methodological procedure adopted in the research was the assessment and classification of articles in the periodical, owned by the House of the Culture in Irati that had the education as central axle. Complete copies of these articles were made, digitalized and organized in a specific data base to the research and then they were analyzed. The research is divided in 3 chapters: The Ideology, State and newspaper (1950); Education in the 1950’s through the periodical Tribuna dos Municípios, and, The newspaper Tribuna dos Municípios and the most focused themes. The research allowed a better understanding on the power of the ideology of the bourgeois State and its continuity, from the typical contradictions of a liberal society, that was affirming itself, in which the education and the press had been a stage for this hegemony.